How Do Stakeholder Groups' Views Vary on Technology in Language Learning?. (15th May 2018) - Trace, Jonathan; Brown, James; Rodriguez, Julio
Abstract : This study examines how technology is perceived by different stakeholder groups in The Language Flagship programs. We administered questionnaires to three stakeholder groups: 14 directors, 34 instructors, and 100 learners at a variety of institutions with three goals: (a) to investigate what technologies the directors, instructors, and learners find useful for language instruction; (b) to explore how and to what degree the perceptions of the directors, instructors, and learners agree about technologies they think use; and (c) to study how learners' views vary with regard to the value of various technologies for language learning inside and outside the classroom.